Regulation of Strengthening of LPD Desa Adat in Bali in A Gap - I Made Suwitra; Diah Gayatri Sudibya (Sociological Jurisprudence Journal, 2019)
The aims of this research is to analyze the implementation of the strengthening of LPDs as a nonbank financial institution in the Desa Adat against various regulations issued by the Government both at the national and regional levels in the perspective of an analytical approach. The basic consideration of this research is that there are still some LPDs that are not healthy and even go bankrupt. The method used is the form of normative legal research with legislation, analytic, case and coexistence approaches. Normatively various regulations issued by the government at the national and regional levels are intended to strengthen the existence of LPDs, but in reality not all LPDs in Desa Pakraman are strong and healthy, some LPDs even went bankrupt. Therefore a comprehensive study of various perspectives is needed in the context of the legal system.